Vaccinations for Anal Squamous Cancer: Current and Emerging Therapies - Berry, John; Glasgow, Sean C. (Clinics in Colon and Rectal Surgery, 2018)
Human papillomavirus (HPV) infection is responsible for 4.3% of the global cancer burden. Since 2006, current HPV vaccines have reduced the prevalence of the virus in adolescent girls, reduced the prevalence of genital warts, and been proven to reduce the progression of anal intraepithelial neoplasia in men. Herein, we review the epidemiology, virology, and immunology behind the prophylactic HPV vaccines and current recommendations for its use. We also review future immune therapies being trialed for use against HPV-related cancers including anal cancer.
Keywords: anal cancer; human papillomavirus; anal intraepithelial neoplasia; anal squamous cell cancer